(untitled) (Research, Society and Development, 2021)
Lignocellulosic materials have been used as bioadsorbents for contaminants removal from industrial effluents due to their physical-chemical properties, renewable source, low-cost and efficiency that make them competitive to commercial activated carbon. The objective of this work is to develop an efficient and low cost bioadsorbent reusing the cashew nut shell (Anarcadium accidentale L), CNS, for the removal of metal ions (Cu2+ and Cr3+). The CNS was characterized by scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), the point of zero charge (pHpzc) and the Boehm titration. The kinetics and adsorption equilibrium experiments were carried out in a monoelementary system, in batch runs at room temperature. The adsorption kinetics was evaluated by the mathematical models of pseudo first-order, pseudo second-order and intraparticle diffusion, while the adsorption isotherm was adjusted according to the Langmuir, Freundlich and Redlich-Peterson models. The removal percentage was 91% (Cu2+) and 96% (Cr3+) and adsorption kinetics was better adjusted to the pseudo second-order model, suggesting the predominance of chemisorption. The fit of the Langmuir isotherm was better for the experimental data of Cu2+ and Cr3+ ions, indicating adsorption in monolayers. It is concluded that the bioabsorbent produced from the cashew nut shell has a high potential for the removal of metals, in addition to being an abundant product in nature, is renewable and biodegradable and its reuse contributes to the reduction of environmental pollution, the production of waste and improves the local circular economy through the valorization of the byproduct.